EFFECT OF PERCEPTION, QUALITY OF SERVICE, RELATIONSHIP MARKETING ON CUSTOMER LOYALTY (Study on BMT Sejahtera Karanganyar, Central Java) - Sumadi Sumadi; Tira Nur Fitria; Ningrum Setyana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to know the effect of service quality, relationship marketing, and perceptions of customers loyalty in BMT Sejahtera. This study uses a quantitative approach to the population of members in the BMT Sejahtera, a sample taken using the calculation of solving formula. Data analysis using multiple linear regression models. T-test result of the study showed that service quality partially had a significant effect on customer loyalty with at count>t table (5,737>1,662). Because the value of t is greater than the value of the t table and the magnitude of the significant value of the P-Value is less than 0.05 (0.00t table (2,022>1,662). Because the value of t is greater than the table value and the value of the significant value of P-Value is less than 0.05 (0.046t table (2,231 > 1,662). Because the value of t is greater than the table value and the significance value of the P-Value is less than 0.05 (0.028